MORAL DALAM NOVEL â€œMEIN ONKEL FRANZâ€ KARYA ERICH KÃ„STNER - KURNIAWAN, ADE (UNIVERSITAS NEGERI SURABAYA, 2016)
Moral to Rachels (2004: 35) is the problems to do something good or bad. Moral teaching is done in the framework of any kind, and is determined by the best reasons for doing so. In the novel, Erich Kästner life story also contains many moral messages that can be a lesson for the reader. Formulation of the problem in this research is: What is the mood in the novel